Improving Literacy: Teacher’s Strategy, and Reading-Deficient Students - Pesino, Aren; Lantaka, Ivy A. (International Journal of Research in Interdisciplinary Studies, 2025)
This study explored how teachers from Grades 1 to 6 at Labuan Central School help students who struggle with reading. It focused on four key teaching strategies: differentiated instruction, clear and consistent routines, positive reinforcement, and hands-on, interactive learning. Using a descriptive-correlational approach, the study gathered data through teacher questionnaires and analyzed it using statistical methods, including Pearson’s correlation. Findings revealed that teachers strongly implement these strategies, especially differentiated instruction, which allows them to adjust lessons based on individual student needs. Consistent classroom routines and positive reinforcement were also widely practiced, helping to create a structured and supportive learning environment. Interactive activities, such as using real-life materials and creative reading tasks, were commonly employed to keep students engaged. However, many teachers still reported that a significant number of students (about 26% to 50%) continue to fall behind in reading. The results showed a weak but statistically significant positive correlation between teaching strategies and students' reading performance. This suggests that while effective teaching methods do contribute to improved literacy outcomes, other factors such as the home environment, student motivation, and access to resources also influence a child's ability to read. The study highlights the importance of instructional strategies while emphasizing the need for broader support, including professional development, adequate school resources, and active community involvement, to fully address the needs of reading-deficient learners.